The Garden of Refugees - Gomes Coelho, Rui (Journal of Contemporary Archaeology, 2017)
Every garden needs to be tendered, and needs a caretaker who knows about the cycles and moods of nature. It is hard to conceive that refugees may have anything to do with gardens, as they are always on the move. In this essay I will examine gardens and refugees. Gardens are not only ecological phenomena but also the articulation of ideas, places and action. They can be places that express the power of humanity over natural circumstances, the projection of an idealized order, or a place of seclusion and escape. That is the reason why gardens are a powerful trope, and that is also why they are sites of entrapment in societies that simultaneously incite and estrange the refugee. I will show that gardens are places in which refugees define some control over their lives, but also where they are rejected. I argue that the conflictive encounters that take place in gardens are better understood when we see them as workplaces, sites in which people produce goods to provide for themselves and their families, and to supply the market. In the end I will defend that the ambiguity of the garden conjures an invitation to us archaeologists: an invitation to glance beyond the narratives of victimhood that reinforce the estrangement of the refugees, and to see the transitory materialities of their lives as mirrors of our own societies.